Predictors of quality of life of Pakistani women with rheumatoid arthritis: a cross-sectional study - Sharma, Sucheta; Eapi, Srilatha; Muqtadir, Abdul; Bokhari, Ammar; Zulfiqar, Mehak; Jiwani, Kinza; Barkat, Rahil (International Journal Of Community Medicine And Public Health, 2021)
Background: Rheumatoid arthritis (RA) is characterized as a chronic inflammatory disease indicated by stiffness, pain, inflammation, and impaired mobility. This results in joint impairment, poor workability, productivity, and afterward, it curtails the quality and expectancy of life of an individual. The aim of this research is to assess the quality of life of Pakistan women with RA and assess various factors affecting it. Methods: It was a cross-sectional study conducted in the Orthopedics department of the Indus Hospital and Health Network, Karachi Pakistan, where we assessed quality of life in sample of women with RA. A consecutive sampling technique was used to enrol women with rheumatoid arthritis who were seen in the Orthopedics outpatient clinic during the study period (February to May 2021). Results: Of the 134 women with RA, 72.39% of women were unemployed, 54.48% of women had family monthly income of 16000 PKR or more and 44.03% of women reported at least one comorbidity other than RA. According to linear regression analyses, women having RA with severe disease activity tended to have tended to have low physical functioning, vitality, emotional wellbeing, social functioning, pain and general health as compared to patients with remission, low disease and moderate disease activity. Absence of family support in disease management can impact vitality and emotional wellbeing with decrease in scores of -85.20 and -120.66 respectively. Conclusions: Guidelines need to developed and implemented for assessing psychological domains of these patients for assessment of quality of life. This will help in maintaining and improving QoL of women with RA.